On Coordinated Control of OLTC and Reactive Power Compensation for Voltage Regulation in Distribution Systems With Wind Power - Salih, Shemsedin Nursebo; Peiyuan Chen (IEEE transactions on power systems, 2016)
Active management strategies such as coordinated on load tap changer (OLTC) voltage control and reactive power compensation (RPC) are frequently suggested for voltage regulation in a distribution system with a high level of distributed generation (DG). This paper proposes a control and coordination algorithm for these two active management strategies. Voltage control through OLTC is achieved by using state estimation (SE) to determine the voltage in the network. To lower the implementation cost of the proposed control strategy, pseudo-measurements are used together with real-time measurement data in the SE. Moreover, the deadband of the automatic voltage control (AVC) relay is relaxed so that the AVC relay acts on the network's maximum or minimum voltage obtained through the SE. This is found to be simpler to realize than adjusting the set point of the AVC relay. Voltage control through RPC is actualized by using integral controllers implemented locally at the wind turbine site. Furthermore, RPC from the local wind turbine is also used to mitigate an overvoltage at a remote bus on the same feeder when the remote wind turbine reaches its regulation limit. The applicability of the proposed voltage regulation algorithm is successfully demonstrated using a case study system.